Performance analysis of a symmetric cryptography algorithm on GPU and GPU cluster - Pousa, Adrián
This article presents a performance analysis of the symmetric encryption algorithm AES (Advanced Encryption Standard) on a machine with one GPU and a cluster of GPUs, for cases in which the memory required by the algorithm is more than that of a GPU. Two implementations were carried out, based on C language, that use the tool CUDA in the case of a single GPU and a combination of CUDA and MPI in the case of the cluster of GPUs. The experimental work carried out shows how communications in the GPU cluster negatively affect algorithm total computation time.